A Closer Look on Lecturer’s Organizational Commitment and Job Satisfaction: A Survey on Selected University - Prastyo, Eko; Hidayat, Dylmoon (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
Lecturers are human resources who have the main role in higher education. However, as significant assets of higher education, lecturers often indicate a low level of job satisfaction and organizational commitment, which is caused by unprofessional and disproportionate task load division procedures and systems as well as ineffective leadership styles which then lead to the intention of lecturers leaving the organization. Therefore, this study aims to examine the effects of instructional leadership and task load on lecturers’ organizational commitment and job satisfaction. This is an experimental study which uses quantitative methods by using a structured questionnaire that is distributed to 60 lecturers who work at the Dental Faculty of IIK Bhakti Wiyata Kediri. The Partial Least Square (PLS) is used in this study as a statistical tool to test research hypotheses. The findings indicate that instructional leadership has positive effects on organizational commitment (p = 0.297) and job satisfaction (p = 0.301), while task load has negative effects on organizational commitment (p = -0.553) and job satisfaction (p = -0.364). These findings have implications for the importance of the ability of leaders in higher education to be able to manage proportional and fair workload assignments to increase lecturers’ organizational commitment to the organization. The findings also encourage the ability of leaders in higher education to be able to build closer social relationships with lecturers both psychologically and emotionally to understand their level of job satisfaction in order to achieve organizational goals effectively.